2021
DOI: 10.1111/jgh.15658
|View full text |Cite
|
Sign up to set email alerts
|

Drainage of pancreatic fluid collections using a lumen‐apposing metal stent with an electrocautery‐enhanced delivery system

Abstract: BenedictDevereaux is a consultant and member on advisory board for Boston Scientific. Milan Bassan is a consultant for Boston Scientific. Payal Saxena is a consultant for Boston Scientific. Thawee Ratanachu-EK is a proctor for Boston Scientific. All other authors have no relevant conflicts of interest to disclose. Financial support: There were no sources of financial grants or other funding for this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Based on quantitative measurement using Egger's test as well as visual inspection of the funnel plot, there was no significant evidence of publication bias in reporting adverse events (Figure 3). The rates of bleeding 25,[27][28][29][32][33][34][35] showed TA B L E 2 Summary of studies included in the meta-analysis a similar tendency, with a pooled OR of 1.35 (95% CI 0.72-2.53; p = 0.36) and potential heterogeneity between the studies (p heterogeneity = 0.05 and I 2 = 49%). The results were consistent when three studies including the initial surgical approach were excluded from the analysis (Table 4).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Based on quantitative measurement using Egger's test as well as visual inspection of the funnel plot, there was no significant evidence of publication bias in reporting adverse events (Figure 3). The rates of bleeding 25,[27][28][29][32][33][34][35] showed TA B L E 2 Summary of studies included in the meta-analysis a similar tendency, with a pooled OR of 1.35 (95% CI 0.72-2.53; p = 0.36) and potential heterogeneity between the studies (p heterogeneity = 0.05 and I 2 = 49%). The results were consistent when three studies including the initial surgical approach were excluded from the analysis (Table 4).…”
Section: Resultsmentioning
confidence: 70%
“…28,29,[32][33][34] The summary of pooled ORs according to the treatment approach is shown in Table 4. Based on eight studies, 25,[27][28][29][32][33][34][35] the rate of adverse events was comparable, with a pooled OR of 1.41 (95% CI 0.66-3.01; p = 0.38; Figure 2) for early interventions compared to delayed interventions, though the data were heterogeneous between the studies (p heterogeneity < 0.01 and I 2 = 82%). Based on quantitative measurement using Egger's test as well as visual inspection of the funnel plot, there was no significant evidence of publication bias in reporting adverse events (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…A survey found that 16 of 22 advanced endoscopists believed that LAMS should be the standard of care for WON [ 44 ]. Khan et al noted that EUS-guided PFC drainage with LAMS was effective in all 4 classifications of PFC, with a technical success rate of 202/208 (97.1%) [ 45 ]. Anderloni et al evaluated the safety of the largest available diameter LAMS (22 mm) [ 46 ].…”
Section: Drainage and Stent Typesmentioning
confidence: 99%
“…The HOT AXIOS stent was developed to enable the endoscopist to an immediate release of the stent following an access to the target lumen with a stent-loaded delivery catheter using the electro-cautery tip under endoscopic ultrasound instead of a needle or guidewire insertion or preliminary dilation ( 3 , 5 , 8 ). The operation process of HOT AXIOS stent mainly includes two steps: cyst puncture and stent release.…”
Section: Design Of Ec-lams and Procedures Processmentioning
confidence: 99%
“…In a nationwide survey from Italy, 97.2% of endoscopists perform LAMS positioning for PFC ( 13 ). The performance of EC-LAMS can reach high technical rate of 97.1%, clinical success rate of 88.8%, and cumulative adverse effects (AE) of 18.3% (7.4% for stent migration, 7.9% for stent occlusion and infection, 2% for major bleeding, and 1% for buried stents) ( 8 ). Factors related to higher risks of AEs include pre-procedural evidence of pancreatic duct leak/disruption, vessel alteration, requiring percutaneous drainage, or a multigate technique, and as well hospital volume is significantly associated with improved outcomes ( 14 , 15 ).…”
Section: Indications and Outcomes Of Ec-lamsmentioning
confidence: 99%